The Influence of Students' Mastery of Vocabulary on Paraphrasing Ability - Muhammad Muslih (Universitas Veteran Bangun Nusantara, 2021)
Some countries much use English as an international language all over the world. Unfortunately, the use of English in some countries is different from each other. In this case, Indonesia uses English as a foreign language. There are four English skills, listening, speaking, reading, and writing. The mastery of vocabulary is a vital aspect in learning a language; we will not be able to speak to read, and write any language if we do not master it in vocabulary. Therefore, vocabulary has an essential role because it is his primary instrument of language. The student's mastery of English vocabulary is still low. Some factors that cause why the students' vocabulary is still low are the teacher's technique that does not motivate students in learning English. Instrument of the collecting data used by the writer is observation, interview, and test. In doing research, the writer uses a quantitative approach. It means that the data being obtained are presented by number and then interpreted by using statistical analysis. The conclusion of the research is the application of mastery of vocabulary on ability in making paraphrase. It is is know the result the student' of the mastery of vocabulary (X variable) in the average of 71.142 and the result the students' of ability in making paraphrase (Y variable) in the average of 68.00. Correlation of C variable on Y variable showing 0.418%. It means that 0.418 is enough to influence the correlation between applying the students' mastery of vocabulary on their ability to make paraphrase.